Comparison of novel oral anticoagulants versus warfarin for post-operative atrial fibrillation after coronary artery bypass grafting. (October 2020) - Manuel, Lucy; Fong, Laura S.; Ang, Zhen Hao; Grant, Peter
Abstract: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was 'Does the use of Novel Oral Anticoagulants (NOACs) result in more complications than Warfarin for treatment of post-operative atrial fibrillation (AF) following coronary artery bypass grafting (CABG)?' Altogether more than 93 papers were found using the reported search with 4 studies representing the best evidence to answer the clinical question, including 1 randomised trial and 3 retrospective case-control studies. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers were tabulated. Timing for initiation of anticoagulation was similar across the studies, with both demonstrating longer hospital stays and greater time to reach therapeutic anticoagulation in the warfarin cohort. Three studies reported similar safety between the two groups. One study revealed significantly more invasive interventions for pleural or pericardial effusions in the NOAC group, whilst in contrast another study demonstrated a higher rate of major bleeding in the warfarin cohort. Cost-analysis revealed that NOACs were overall more cost-effective compared to warfarin despite the higher cost for the medication itself. In conclusion, the use of NOACs after CABG for post-operative AF can be used as an alternative to warfarin, however, one should remain vigilant for possible pericardial or pleural effusions which may require reintervention. Further dedicated research and larger appropriately powered randomised control trials are needed to confirm the safety of NOACs in post-cardiac surgery patients. Highlights: Atrial fibrillation (AF) is the most common arrhythmia post cardiac surgery. While usually self-limiting, AF has increased morbidity and mortality to patients. Anticoagulation is warranted if AF is persistent or recurrent. Warfarin has been the mainstay of therapy, however, NOACs have gained popularity. The safety of NOACs in post-cardiac surgery patients is so far poorly defined.